PENGARUH PENDEKATAN KETERAMPILAN PROSES TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SUGESTIF DI SEKOLAH DASAR - Irwani, Windra; Marzuki, Marzuki; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to analyze the influence of the process skills approach on the writing skills of suggestive narrative essays in grade III 09 elementary schools learning Indonesian in western Pontianak. The method used to experiment with the Quasi Experimental design and non equivalent control group design. The population of all students is 147 people. The sample of this study was class IIIA students, amounting to 39 people as an experimental class and class IIIB students as a control class totaling 37 people. Data collection techniques used are measurement techniques and data collection from the essay writing test. Based on data analysis, the average post test results of the experimental class were 78.69 and post test controls at 74.79. Hypothesis test results using t-test (surveyed variance) get a count of 2.653 t = as for the level of freedom (39 + 37-2 = 74) with a significant level ? = 5% obtained t = 1.668 tables, which means t count> t table, This proves that there is an effect of applying the process skills approach to the ability to write suggestive narrative essays in Indonesian language learning. Based on the calculation of the effect size (ES) get ES = 0.45 which includes the medium criteria. Keywords: Influence, Process Skills Approach, Writing Skill, Indonesian Learning